XMM-Newton observations of 1A 0535+262 in quiescence - Doroshenko V; Santangelo A; Doroshenko R; Caballero I; Tsygankov S; Rothschild R (France, 2025)
Accretion onto magnetized neutron stars is expected to be centrifugally inhibited at low accretion rates. Several sources including 1A 0535+262, however, are known to pulsate in quiescence at luminosities below the theoretical limit predicted for the onset of the centrifugal barrier. Here we present the results of an analysis of a similar to 50 ks long XMM-Newton observation of 1A 0535+262 in quiescence. At the time of the observation, the neutron star was close to the apastron, and the source had remained quiet for two orbital cycles. In spite of this, we detected a pulsed X-ray flux of similar to 3 x 10(-11)erg cm(-2) s(-1) . Several observed properties, including the power spectrum, remained similar to those observed in the outbursts. Particularly, we have found that the frequency of the break detected in the quiescent noise power spectrum follows the same correlation with flux observed when the source is in outburst. We argue that, along with other arguments previously reported in the literature, our results suggest that the accretion in quiescence also proceeds from an accretion disk around the neutron star.
Physics at the Magnetospheric Boundary